SOSIALISASI PROGRAM KOTA LAYAK ANAK DI KOTA PEKANBARU (STUDI KASUS : HAK SIPIL ANAK) - Desiana, Nilawati; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Pekanbaru is one of the cities that have been honored as the Child-Friendly City (CFC) given by the Ministry of Women and Child Development. Population and Civil Registration Agency is one of the agencies that took the role in socializing child-Friendly city program, in this case Population and Civil Registration Agency is responsible in fulfillment of children’s civil right. The purpose of this research is to find out how the socialization of child-friendly city program in Pekanbaru and what factors affecting that sosialization. The information about fulfillment of a child’s civil right.This research use grand theory of Harold D. Laswell (Effendy 2005:10) which is there are five indicators on it: 1.) Who (who said), 2.) Say What (what message to say), 3.) In Which Channel ( the media), 4.) The Whom ( to whom it is addressed ), 5.) With What Effect (effect/impact).The results of research in the field said socialization that Population and Civil Registration Agency did are not optimal yet because there are still many society who do not know about child-friendly city program in civil right. If the socialization optimally done optimally then it will provide a good influence to Pekanbaru society with the child-friendly city in Civil Rights.Keywords : Socialization Program, City for Children, Civil Rights of the Child